Default and interest rate shocks: Renegotiation matters - Victor Almeida; Carlos Esquivel; Timothy Jerome Kehoe; Juan Pablo Nicolini (Rutgers University, Department of Economics, 2024)
We develop a sovereign default model with debt renegotiation in which interest-rate shocks affect default incentives through two mechanisms. The first is the standard mechanism through which higher rates tighten the budget constraint. The second rests on how risk-free rates affect lenders' opportunity cost of holding delinquent debt. When rates are high, this cost increases and lenders accept larger haircuts, which makes default more attractive ex-ante. We use the model to study the 1982 Mexican default, which followed a large increase in US interest rates. Our novel renegotiation mechanism is key for reconciling sovereign default models with the narrative that US monetary tightening triggered the crisis.
Keywords: F34; F41; 330; Sovereign default; Renegotiation; Interest rate shocks